Caracterización clínica y epidemiológica de cefalea tensional episódica frecuente en funcionarios del Gobierno Provincial de Loja periodo enero - junio 2016. - Rivera Ramírez, Fátima Dayanna (2017)
Frequent episodic tension headache is included within primary headache according to the International Headache Society (IHS), with well-defined criteria, being a problem for the people who suffer it with repercussions on their quality of life; for this reason the present investigation has the purpose of: establish clinical manifestations, define epidemiological characteristics and their relationship to frequent episodic tension headache; the present study was of a cross-sectional and prospective type, carried out in the Gobierno Provincial de Loja, through the application of two surveys with prior informed consent, the first one encompasses the clinical manifestations according to the diagnostic criteria of the III Edition of the International Classification of Headaches (ICHD-III), with that the group that was part of the study was determined constituting a sample of 71 officials of 156 that work in the public entity; then the second survey on epidemiological characteristics was applied to this group, obtaining the following results: the most frequent clinical manifestations were: bilateral cranial pain in 96% (n=68), of expressive or intensive quality in 100% (n=71), headache does not worsen with usual physical activity in 90% (n = 64). Regarding the epidemiological characteristics: The mean age was between 31 and 48 years of age in 76% (n = 54), 89% (n = 63) had a higher education level, the main factor triggering headache was stress or mental tension in the 90% (n = 64). The present study reveals the high prevalence of episodic tension headache within occupational diseases. Key words: Frequent episodic tension headache, clinical manifestations, epidemiology.